The study of musculoskeletal symptoms in diabetic patients with Nordic questionnaire - D. S., Ashwini; A. N. , Ravichethan Kumar; L. , Harshvardhan (International Journal of Research in Medical Sciences, 2023)
Background: A variety of musculoskeletal conditions have been associated with diabetes mellitus which involves multiple joints affecting activities of daily living. It warrants screening of such symptoms in patients with diabetes mellitus in routine health checkup and to address such complaints. Using a simple questionnaire such as Nordic questionnaire which can aid in studying presence or absence of musculoskeletal symptoms in diabetic patients and to know the frequently involved joint. Methods: Cross sectional data of 156 adults with type 2 diabetes mellitus attending tertiary hospital were examined. The patient’s demographic details were collected. Musculoskeletal pain was assessed using Nordic questionnaire. Multiple logistic regressions were used to examine risk associated with musculoskeletal pain. Results: The study showed that prevalence of musculoskeletal pain was 64.1%. The participants mean age was 50.57 years. The study group contained 48.7 % females and 51.3% males. The mean BMI was 27.56kg/m2 with mean HBA1c of 9.29%. 26% of the study population had significant discomfort in last 7 days which was interfering with their work. Majority of them (73%) had suffered shoulder pain. Presence Of musculoskeletal symptoms showed association with HbA1c, BMI, and waist circumference. There was no association between joint pains with respect to years of job Conclusions: Musculoskeletal symptoms are frequent in diabetic patients. Addressing such complaints is important to screen pathology related to joint and surrounding soft tissue on routine check-up, thus preventing future complication which may result in disability by using simple Nordic questionnaire.